Roles of the NLRP3 inflammasome in the pathogenesis of diabetic nephropathy - Qiu, Yuan-ye; Tang, Li-qin (Pharmacological research, 2016)
[Display omitted] Diabetic nephropathy (DN) is a serious complication of diabetes mellitus, and persistent inflammation in circulatory and renal tissues is an important pathophysiological basis for DN. The essence of the microinflammatory state is the innate immune response, which is central to the occurrence and development of DN. Members of the inflammasome family, including both “receptors” and “regulators”, are key to the inflammatory immune response. Nucleotide binding and oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3) and other inflammasome components are able to detect endogenous danger signals, resulting in activation of caspase-1 as well as interleukin (IL)-1β, IL-18 and other cytokines; these events stimulate the inflammatory cascade reaction, which is crucial for DN. Hyperglycaemia, hyperlipidaemia and hyperuricaemia can activate the NLRP3 inflammasome, which then mediates the occurrence and development of DN through the K+ channel model, the lysosomal damage model and the active oxygen cluster model. In this review, we survey the involvement of the NLRP3 inflammasome in various signalling pathways and highlight different aspects of their influence on DN. We also explore the important effects of the NLRP3 inflammasome on kidney function and structural changes that occur during DN development and progression. It is becoming more evident that NLRP3 inflammasome targeting has therapeutic potential for the treatment of DN.